(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This work offers the complete index of Actas del I Coloquio sobre lenguas y culturas prerromanas de la Península Ibérica, an instrument that improves the workability and accessibility of contributions made of the Symposium of which had been published only those of J. Corominas.